Idiomatic Expressions Found in Taylor Swift's Song 'All Too Well (10 Minute Version)’ - Kadek Ayu Siwi Patmawati; I Gusti Agung Sri Rwa Jayantini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research analyzes idiomatic expressions in Taylor Swift’s song